2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35082
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Future Workforce of Architecture, Engineering, and Construction for Robotic Automation Processes

Abstract: FIU), College of Engineering and Computing and teaches at the Moss School of Construction, Infrastructure and Sustainability. Dr. ElZomor completed his doctorate at Arizona State University (ASU), Ira A. Fulton Schools of Engineering. Prior to attending ASU, Dr. ElZomor received a master's of science degree in Architecture from University of Arizona, a master's degree in Engineering and a bachelor of science in Construction Engineering from American University in Cairo. Dr. ElZomor moved to FIU from State Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The authors used SPSS software to develop the regression model. The outcome of the dependent variable, AEC students’ interest to learn the SF concept, has ordinal values, therefore this study selected the ordinal probit regression method for the analysis (Elzomor et al , 2020). Because this is a pilot study for integrating SF in the curricula, the confidence interval is assumed to be 90% for the regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The authors used SPSS software to develop the regression model. The outcome of the dependent variable, AEC students’ interest to learn the SF concept, has ordinal values, therefore this study selected the ordinal probit regression method for the analysis (Elzomor et al , 2020). Because this is a pilot study for integrating SF in the curricula, the confidence interval is assumed to be 90% for the regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Review papers and all papers related to robotics mentioned the need to incorporate more skills related to IOP Publishing doi:10.1088/1755-1315/1101/8/082032 7 programming and computational thinking. This seems to relate to the need for students to understand robotics concepts [24], [25], [26], or the influence of parametric modelling [26], [27].…”
Section: Robotics Push For Programming Skills and Computational Think...mentioning
confidence: 99%
“…Focusing on improving robotics skills for future construction professionals, ElZomor et al [24] have also explored industry professionals' views in the adoption of robotics and automation in AEC and based on their findings have developed a series of mini courses about robotics. Their course also incorporates teaching students about AEC related robots, VR and AR, programming and the use of machine learning.…”
Section: Robotics Push For Programming Skills and Computational Think...mentioning
confidence: 99%
“…The unskilled workforce is one of the major barriers that impact the adoption of automation and robotics technology in the construction industry [4]. The shortage of a skilled workforce can be addressed through a paradigm shift in construction education towards developing students' technological skills and improving their ability to communicate technological knowledge [5]. For instance, a study demonstrated the efficacy of infusing technology in construction education by integrating Virtual Reality technology to promote interpersonal growth and address students' presentation skills deficiencies [6].…”
mentioning
confidence: 99%
“…There are several applications of 3D printing in an academic setting that includes: (1) to produce artifacts that aid learning materials; (2) to create assistive technologies; (3) to teach students about how 3D printing technologies work; (4) to teach instructors about 3D printing technologies; (5) to use it as a support technology during teaching; and (6) to support outreach activities [9]. Although there are several online materials that could help students explore 3D printing technologies, there is a lack of an appropriate textbook and pedagogical approach for assisting students in developing such technological skills.…”
mentioning
confidence: 99%